JARINGAN PEREDARAN NARKOBA DI KALANGAN REMAJA KOTA SURABAYA - Prameswary, Lintang Sarashaty (Paradigma, 2021)
The large number of teenagers as drug users is caused by the distribution of drugs that is increasing and spreading everywhere. Drugs are also easy to buy, in addition to that due to global policies regarding regulations that suppress drug trafficking and trafficking. Drug users among teenagers, especially high school students are found and this is the highest level of juvenile delinquency. Economic problems can also influence teenagers to become drug dealers. The purpose of this study is to identify how the objective conditions of drug network actors are, identify the status and role of each actor, and identify interactions between drug network status among adolescents. This study uses a qualitative approach with an ethnomethodological perspective, the researcher uses an ethnographic model and the theory of the Delinquency Subculture by Albert K. Cohen. The data obtained were carried out by participatory observation and in-depth interviews. The results of this study indicate that the factors that influence adolescents to deviate are environmental and economic factors, the social network formed is an informal social network because it is formed from integration between friends. Keywords: Network, Drugs, Teenager